Critique and System: Early and Late Natorp’s Philosophy - Hernán Pringe (RUDN Journal of Philosophy)
This paper presents an interpretation of the connection between Natorp’s early and late philosophy. An analysis of two versions of Natorp’s deduction of categories shows the consistent development of Natorp’s thought. Each deduction expresses, in Natorp’s words, a direction of movement between the centre and the periphery. The early deduction moves from the periphery to the centre by means of the transcendental method. The critical investigation of the conditions of possibility of mathematical-physical science reveals the structure of thought itself. The late deduction is oriented in the opposite direction, from the centre to the periphery. Thought now develops freely and establishes the systematic character of philosophy. We argue that the two deductions complement each other in a single coherent position that accounts for the relationship between critique and system. Philosophical systematics is conceived as the necessary sequel and culmination of an inquiry, the first part of which is developed according to the transcendental method.